Hurdling with the “New Normal”: Thoughts and Experiences of Parents on the Shape of their Children in the Academe - Alexis Arizabal Enriquez (Unib Press, 2022)
This study is focused on the Thoughts and Experiences of Parents on the Shape of their Children in the Academe as they hurdle in the new normal. Specifically, it sought to analyze their thoughts on the ten questions posited on them that varied from safety of their children in school, module purchase and subsidy, optimum learning despite on the adopted learning system by the school, time to submit finished tasks of their children, academic freeze, and thoughts in case tehir children get sick. Findings included the following: Parents were doubtful as to safety of their children in the school yet, hopeful that through the skills, knowledge, and dedication of their reachers, optimum quality education could still be achieved regaredless of the learning modality which the school implements, subsidy of modules was strongly begged for since an allocation fro materials production is a priority of the school amidst this pandemic, academic freeze wa not an option to a majority, humane considerations from the teachers was a loud remark from parents. This allows their children to analyze, edit, and review materials and assignments. In conclusion, parents’ priority is education of their children that they need to purchase modules at all cost, hopeful that optimum learning and quality education could be achieved through the dedication and commitment of skilled and knowledgeable teachers. It is then recommended that the administration may want to consider conducting an orientation seminar to parents as to the new procedures, policies, modality for learning for teir children, Parents are also recommended to monitor and guide their children especially on the submission of finished tasks and other assignements.